Forced diuresis and dual-phase (18)F-fluorodeoxyglucose-PET/CT scan for restaging of urinary bladder cancers - Harkirat, S (Medknow Publications, 2010)
CONTEXT: The results of (18)F-fluorodeoxyglucose (FDG)-PET imaging carried out with the current standard techniques for assessment of urinary tract cancers have been reported to be less than satisfactory because of the urinary excretion of the tracer. AIMS: To investigate the role of dual-phase FDG-PET/CT in the restaging of invasive cancers of the urinary bladder, with delayed imaging after forced diuresis and oral hydration as the scanning protocol. SETTINGS AND DESIGN: FDG-PET has been considered to be of limited value for the detection of urinary tract cancers because of interference by the FDG excreted in urine. We investigated the efficacy of delayed FDG-PET/CT in the restaging of invasive bladder cancer, with imaging performed after intravenous (IV) administration of a potent diuretic and oral hydration. MATERIALS AND METHODS: Twenty-nine patients with invasive cancer of the urinary bladder were included in this study. Patients were divided into two groups: Group I (22 patients) included cases with invasive bladder cancer who had not undergone cystectomy and group II (seven patients) included cases with invasive bladder cancer who had undergone cystectomy and urinary diversion procedure. All patients underwent FDG-PET/CT scan from the skull base to the mid-thighs 60 min after IV injection of 370 mega-Becquerel (MBq) of FDG. Additional delayed images were acquired 60-90 min after IV furosemide and oral hydration. PET/CT data were analyzed as PET and CT images studied separately as well as fused PET/CT images and the findings were recorded. The imaging findings were confirmed by cystoscopy, biopsy or follow-up PET/CT. RESULTS: The technique was successful in achieving adequate washout of urinary FDG and overcame the problems posed by the excess FDG in the urinary tract. Hypermetabolic lesions could be easily detected by PET and precisely localized to the bladder wall, perivesical region and pelvic lymph nodes. PET/CT delayed images were able to demonstrate 16 intravesical lesions (in 13 patients), with excellent clarity. Lymph node metastases were detected in a total of six patients. Of these, in two patients, FDG-avid lymph nodes were evident only in the delayed images. The information provided by the postdiuretic delayed images changed the PET/CT interpretation in 14 patients of invasive bladder cancer: Recurrent bladder lesions were identified in 12 patients, pelvic lymph node metastasis (only) in one patient and bladder lesion as well as lymph node metastasis in one patient. Distant metastases were detected by PET/CT in two cases. CT scan was false-negative for early recurrence in the bladder wall for seven of 16 lesions. CT also showed two false-positive lesions. There were no false-positives with PET. CONCLUSIONS: Detection of recurrent disease in cases of invasive bladder cancer can be significantly improved by using FDG-PET/CT, with delayed imaging following forced diuresis and oral hydration. Composite PET/CT is superior to CT alone for the restaging of invasive bladder cancers.